2009
DOI: 10.1021/ma9008516
|View full text |Cite
|
Sign up to set email alerts
|

Two DSC Glass Transitions in Miscible Blends of Polyisoprene/Poly(4-tert-butylstyrene)

Abstract: Conventional and temperature-modulated differential scanning calorimetry (DSC) experiments have been carried out on miscible blends of polyisoprene (PI) and poly(4-tert-butylstyrene) (P4tBS) over a broad composition range. This system is characterized by an extraordinarily large T g difference (∼215 K) between the two homopolymers. Two distinct calorimetric glass transitions were observed in blends of intermediate compositions (25%-50% PI) by both conventional and temperature-modulated DSC. Good agreement was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
54
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 32 publications
(78 reference statements)
7
54
0
Order By: Relevance
“…Extensive studies have been conducted for such miscible blends to examine the dynamics of monomeric segments being related to the glass transition. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Those studies revealed characteristic features of the miscible blends such as the broad (almost two-step) glass transition noted in thermal measurements, the broad modes of segmental motion detected with NMR, and the broad and thermo-rheologically complex relaxation processes observed with the dielectric/viscoelastic methods. These features are related to the self-concentration effect 16 and the local composition fluctuation.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies have been conducted for such miscible blends to examine the dynamics of monomeric segments being related to the glass transition. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Those studies revealed characteristic features of the miscible blends such as the broad (almost two-step) glass transition noted in thermal measurements, the broad modes of segmental motion detected with NMR, and the broad and thermo-rheologically complex relaxation processes observed with the dielectric/viscoelastic methods. These features are related to the self-concentration effect 16 and the local composition fluctuation.…”
Section: Introductionmentioning
confidence: 99%
“…Not so frequently, even solid‐state NMR is being used to study the miscibility of polymer blends 11. In a DSC, the existence of a single T g between those of the constituent polymers has been accepted as a general criterion for miscibility while two T g s at the original position represents an immiscible blend 10, 12. According to Kammar et al,13 the typical domain size sensitivity of conventional DSC to phase‐separated polymeric materials is ca.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of modulated differential scanning calorimeter (MDSC) has permitted to understand the polymer miscibility in a better way compared with conventional DSC 15, 16. It is important to note that the polymer blends that are judged miscible based on conventional DSC have shown two calorimetric T g s based on heat capacity ( C p ) results obtained from MDSC 12, 17. The results of these experiments have made clear that the indication of a single T g by DSC is not a universal feature to judge the polymer miscibility 12.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although immiscible blends show distinct glass transition temperatures T g , which could shift with respect to the values of the component polymers [2], the situation is complicated by the presence of two T g , also in miscible blends [3,4]. * In the case of elastomers, the advantages for blending are numerous due to an alternative of synthesizing a new elastomer, older and better-characterized rubbers can be employed, hopefully yielding an ideal complement of properties from the blended materials.…”
Section: Introductionmentioning
confidence: 99%